Differential settlement of associated species on ostrea puelchana D'Orbigny, 1842 (Ostreidae) in Patagonia (Argentina) - Romero, María Virginia (2013)
Ostrea puelchana d?Orbigny, 1842 is a common species of commercial interest in Patagonia and is distributed from Rio Grande do Sul (Brazil) to San Matías Gulf (SMG, Argentina). In SMG, the species develops natural banks that provide irregular surfaces suitable for colonization of organisms. We studied the composition and frequency of encrusting and associated species on O. puelchana shells as well as the preferential settlement of epibionts on different areas within left and right valves. A total of 55 taxa were identifi ed. The dominant groups were Annelida, Foraminifera, Bryozoa and Mollusca in two different oyster banks. The lifestyle of the oyster favors a preferential settlement of epibionts on different valves and areas within the valves. Substratum heterogeneity, reproductive cues, gregarious behavior, protection against predation and/or brooding care could be responsible for this differential settlement. The left valve was more encrusted than the right one. Spirorbinae, Cirratulidae, Foraminifera, juvenile O. puelchana, Bryozoa and Hydrozoa showed preferential settlement in different areas on the external left valves. On the external right valves, the same taxa except for Hydrozoa showed a nonrandom distribution between areas.